Effect of soil moisture on growth and arbuscular mycorrhizal colonization of crops and tree seedlings in alfisol - ANURADHA JHA and V. D. TRIPATHI, ASHOK SHUKLA*, ANIL KUMAR (Indian Phytopathology, 2010)
A study was conducted to investigate the effect of soil moisture levels (field capacity [FC], half field capacity [HFC] and double field capacity [DFC]) on growth and arbuscular mycorrhizal (AM) colonization of two crops (Phaseolus mungo Roxb. var. PU-35 and Triticum aestivum L. var. WH-147) and seedlings of two multi purpose tree species (Eucalyptus tereticornis Sm. [Clone C-7, ITC, Bhadrachalam] and Albizia procera Benth.). Significant increase in plant growth parameters and phosphorus (P) uptake was recorded after inoculations with AM fungi (Acaulospora scrobiculata Trappe, Glomus cerebriforme McGee and G. intraradix Schenck & Smith). Different AM fungi were effective in terms of plant growth and P uptake at different soil moisture levels with most of them having maximum efficacy at FC. Maximum AM activity in terms of arbuscules, vesicles, sporocarp formation, colonization index and spore count per 100 g soil was also recorded at FC in studied plants. While ranking the importance of two factors studied viz., soil moisture levels and inoculation with AM fungi for their effect on the growth of crop/ trees, inoculations with AM fungi ranked first (explaining 33 to 86% variation in plant growth) for P. mungo, T. aestivum and A. procera (forward selection method), whereas soil moisture levels dominantly explained the growth variation in E. tereticornis, except few cases. The results obtained in present study suggest that inoculation of plants with a suitable AM consortium could be more beneficial as compared to individual AM fungi, depending upon the soil moisture content of the fields and plant species.